2001
DOI: 10.1192/apt.7.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for choice of selective serotonin reuptake inhibitor in depressive illness

Abstract: The selective serotonin reuptake inhibitors (SSRIs) are the most extensively studied of the newer antidepressants and are increasingly being used as first-line treatment for depression (Anderson et al, 2000). In this article we concentrate on issues that need to be taken into account when selecting one of the five SSRIs marketed in the UK (citalopram, fluoxetine, fluvoxamine, paroxetine and sertraline) for individual patients. We have concentrated on treatment of depression and have not reviewed their use in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
1
8
1
2
Order By: Relevance
“…9 In a systematic review on SSRIs as the first line treatment, Anderson and Edwards reported no difference in sexual dysfunction in the patients taking citalopram, fluoxetine, fluvoxamine and sertraline. 17 In our study, sexual function significantly decreased after treatment with citalopram. Also the results showed that erection, satisfaction, libido and ejaculation decreased significantly after treatment with citalopram.…”
Section: Discussionsupporting
confidence: 51%
“…9 In a systematic review on SSRIs as the first line treatment, Anderson and Edwards reported no difference in sexual dysfunction in the patients taking citalopram, fluoxetine, fluvoxamine and sertraline. 17 In our study, sexual function significantly decreased after treatment with citalopram. Also the results showed that erection, satisfaction, libido and ejaculation decreased significantly after treatment with citalopram.…”
Section: Discussionsupporting
confidence: 51%
“…However, they included only five trials involving fluvoxamine, and their review is now outdated. The clinical guideline released by the same authors (Anderson and Edwards, 2001) suggested that fluvoxamine was not the best choice of SSRI in routine practice because of relatively high discontinuation rate, but this statement needs to be moderated. It is, therefore, very hard for us to speculate why fluvoxamine is less popular than the other SSRIs (Kadusevicius, et al, 2006;Lawrenson, et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…24 Citalopram and sertraline are among the more specific agents and in vitro studies suggest they are least likely to inhibit these iso-enzymes. A recent survey of rehabilitation consultants and geriatricians in the UK 23 has demonstrated these two agents to be the most common first choice for management of depression following ABI at present.…”
Section: Choice Of Antidepressantmentioning
confidence: 99%